Cultivating the desert: irrigation expansion and groundwater abstraction in northern state, Sudan - Fragaszy, S.; Closas, Alvar (2016)
This study examines the socioeconomic features that underpin the expansion of groundwater-dependent irrigation in Northern State, Sudan. Groundwater development in the region serves as an economic lifeline given the poor Nile-based irrigation infrastructure and future changes in Nile hydrology. Groundwater-dependent irrigation is found to be expanding in previously uncultivated regions increasingly distant from the Nile. The study finds these historically marginal lands are targeted for capital-intensive agricultural projects because landholding patterns in traditionally cultivated areas preclude new large developments and improved infrastructure has lowered farming costs in distant terraces. Private companies and large landholders have a history of successful agricultural ventures in Northern State and are reliant on easily accessible and reliable groundwater resources for these new farms.